Religious Orthodoxy and the American Worker - Steffy, Kody (Sociology of religion, 2013)
Inspired by Weber's classic writings on religion and economic ethics and guided by moral cosmology theory's conceptualization of religious orthodoxy, this article responds to recent calls for renewed interest in religion and work. Analyzing data from the Economic Values Survey, it documents the complex ways that religion influences American workers. This study contributes to the sociologies of religion and work, along with the field of organizational behavior, in two ways. First, it shows that moral cosmology theory applies to an important sphere of social life: the workplace. Second, contrary to those who argue that religion serves a more therapeutic than directive role in the workplace, it shows that religious orthodoxy shapes work behaviors, orientations, and decision-making. In doing so, this article also contributes to the emerging literature in management studies regarding the role of the sacred in secular organizations.